PRACTICAL APPROACHES TO CALCULATING THE RELIABILITY OF MULTIPLE- BOLT JOINTS OF THE SILO BODY SHEETS (Collection of scientific works «Modern structures of metal and wood», 2020)
This article discusses the issues of practical probability calculation of failure-free operation  of  quasihomogeneous  bolted  joints  of  steel  silo  body  sheets.  The  heterogeneity  of  the joints of silo thin-sheet structures can be caused by a number of reasons, the most common of which are installation errors, for example, the presence of a beyond-design strength class in the bolt joint.  Such  a defect will  cause an  increase  in the risk  of  failure, to quantify the  value of which  is  not possible,  according  to  existing  engineering  methods  or  guidelines  of  regulatory  documents.  It  is more logical in this direction to use probabilistic methods of calculation, which, firstly, give a more justified economic result, and secondly, depending on the adopted indicator, can be a qualitative and quantitative characteristic of any parameter. As part of this problem, the reliability calculation of the joint was performed by determining a random value of the critical variable coefficient. The value of this parameter was taken equal to the ratio of the random value of the generalized stress to the random value of the joint bearing capacity. In the presented example of a bolted joint of thin-sheet  silo  structures,  the  critical  variable  coefficient  was  determined  according  to  the  author's technique  from  a  system  of  conditions  under  which  the  reliability  of  an  inhomogeneous  joint  is observed. The article also investigated the dependence of the level of joint reliability when varying the  number  of  beyond-design  bolts.  The  results  of  changes  in  the  probability  of  failure-free operation and the behavior of the reliability graphs are illustrated in the graphs as a set of critical variable  curves  on  a  critical  probability  scale.  The  choice  of  this  visualization  is  based  on  the simplicity and clarity of the presentation of the results received. The study showed that with a small number of “replacement” bolts, they are the main reason for the failure of the joint; however, with an  increase  in  the  number  of  beyond-design  bolts,  the  fracture  mechanism  will  depend  on  the probabilistic justification of the load and strength.